A new species of Colobothea Lepeletier & Audinet-Serville, 1825 (Coleoptera, Cerambycidae, Lamiinae) from Peru, French Guiana, and Brazil, with notes on Colobothea hirtipes (Degeer, 1775) - Tavakilian, Gérard L.; Santos-Silva, Antonio (Zootaxa, 2022)
Colobothea batesi sp. nov. is described based on specimens from Peru, French Guiana, and Brazil. Photographs of the male holotype and one female paratype are provided, as well as photographs of a male and a female of C. hirtipes (Degeer, 1775) to facilitate comparison. Notes on host plants of C. hirtipes are also provided.